2016
DOI: 10.1038/srep29661
|View full text |Cite
|
Sign up to set email alerts
|

Phonon dispersions and Fermi surfaces nesting explaining the variety of charge ordering in titanium-oxypnictides superconductors

Abstract: There has been a puzzle between experiments and theoretical predictions on the charge ordering of layered titanium-oxypnictides superconductors. Unconventional mechanisms to explain this discrepancy have been argued so far, even affecting the understanding of superconductivity on the compound. We provide a new theoretical prediction, by which the discrepancy itself is resolved without any complicated unconventional explanation. Phonon dispersions and changes of nesting vectors in Fermi surfaces are clarified t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 62 publications
7
26
2
Order By: Relevance
“…The T c of BaTi 2 Sb 2 O has been estimated by Subedi and Nakano et al using the Allen-Dynes formula, and found to be 2.7 K and 2.30 K, respectively [43,47]. The estimated T c is almost consistent with the experimental value (T c = 1.2 K), suggesting BaTi 2 Sb 2 O is a conventional BCS-type superconductor.…”
Section: Isovalent Substitution Effect On Bati2pn2osupporting
confidence: 76%
See 3 more Smart Citations
“…The T c of BaTi 2 Sb 2 O has been estimated by Subedi and Nakano et al using the Allen-Dynes formula, and found to be 2.7 K and 2.30 K, respectively [43,47]. The estimated T c is almost consistent with the experimental value (T c = 1.2 K), suggesting BaTi 2 Sb 2 O is a conventional BCS-type superconductor.…”
Section: Isovalent Substitution Effect On Bati2pn2osupporting
confidence: 76%
“…The three-dimensional hole sheet located around the R point is derived from the mixture of three d orbitals, where the sheet compensates other two electron sheets reflecting that an even electron count in BaTi2Sb2O. Consistent results for the FS of BaTi2Sb2O were also obtained in other theoretical studies [41][42][43]. The electronic structure for BaTi2Bi2O have been obtained by Suetin et al, [44].…”
Section: Electronic Structure Of Bati2pn2osupporting
confidence: 69%
See 2 more Smart Citations
“…[8,9] The predictions were, however, found to be seriously depending on the choice of empirical force fields [10]. Ab initio approaches [11,12] are expected to exclude such ambiguity, and are getting to be feasible realized by the implementations of phonon analysis especially those beyond the harmonic approximation [13]. Such approaches have been applied to inorganic crystalline materials such as semiconductors, [13][14][15] achieving the predictions fairly coinciding with experiments over the range, 1-10 2 W/mK.…”
Section: Introductionmentioning
confidence: 99%